Low-temperature hydrothermally treated Eucalyptus globulus bark: From by-product to horticultural fiber-based growing media viability - Chemetova, C. (2021)
Worldwide, the circular economy approach increased the need of waste-streams minimization, promoting byproducts re-circulation into the value chain which creates sustainable industrial synergies. Eucalyptus globulus bark fiber is a waste from pulp and paper industry that can be re-used in horticultural applications. This work aims to use low-temperature hydrothermally treated E. globulus bark as a fiber material for growing media formulation. Three types of bark fiber were used: industrial E. globulus fresh bark (IB) ground to output sieve of 6 × 6 mm, and two low-temperature hydrothermally treated barks (TB60: 60 ◦C, 20 min; TB100: 100 ◦C, 40 min). The three fiber materials were blended at 25 and 50% (v v 1) (B25; B50) with peat. IB was phytotoxic for Cress (Lepidum sativum) seeds, causing low germination (91%) and root growth inhibition. TB60 and TB100 reduced significantly phytotoxicity with germination rates of 98 and 100%, and Munoo Liisa index around 90% compared to commercial substrate. A pot experiment using Chinese cabbage (Brassica rapa ssp. pekinensis) as a model plant, revealed lower germination (95%) in IB blends than in treated ones and in commercial substrate (CS) (98–100%), reinforcing the IB phytotoxicity. B50 decreased water retention, and reduced plant growth due to nitrogen immobilization inherent to woody biomass. B25 showed shoot weight, and root growth statistically equal or higher than CS, encouraging use of this blending proportion of low-temperature hydrothermally treated bark in future growing media formulation. Circular horticulture approach is applied through the present fiber valorization into substrate component